North Carolina macular dystrophy shows a particular drusen phenotype and atrophy progression. Issue 9 (30th March 2021) - Birtel, Johannes; Gliem, Martin; Herrmann, Philipp; Neuhaus, Christine; Holz, Frank G; MacLaren, Robert E; Scholl, Hendrik P N; Charbel Issa, Peter
Abstract : Background/Aim: To provide a comprehensive multimodal retinal imaging characterisation of patients with North Carolina macular dystrophy (NCMD). Methods: Clinical evaluation and retinal imaging in six families. Results: Twenty-one subjects showed phenotypic characteristics of NCMD . Small drusen-like deposits were found in all affected individuals, either tightly grouped in the macula, or surrounding atrophic or fibrotic macular alterations. These small subretinal lesions showed an increased fundus autofluorescence and were associated with only mild irregularities on optical coherence tomography imaging. Similar drusen-like deposits were regularly seen in the peripheral fundus, predominantly temporally and often with a radial distribution. Two patients showed a bilateral chorioretinal atrophy and two had a macular neovascularisation (MNV). Findings from follow-up examinations were available from 11 patients. The retinal phenotype remained overall stable, except for two patients: one patient with atrophy showed a distinct growth of the atrophic lesions on longitudinal AF imaging over a review period of 14 years. One patient with MNV showed a unilateral decline of best-corrected visual acuity. Genetic testing identified the single nucleotide variant chr6:100040987G>C upstream of the PRDM13 gene in all family members with NCMD phenotype. Conclusion: Patients with NCMD show a characteristic retinal phenotype and distribution of drusen that differ from drusen in patients with age-related macular degeneration. Although the prognosis of this developmental condition is overall better than for other macular diseases with drusen, patients may be at risk of developing MNV or enlargement of pre-existing atrophy.